Ocean ridges and trenches - Aleshire, Peter; Nash, Geoffrey H. (New York : Chelsea House, 2007)
Provides information about the formation of ocean ridges and trenches. Includes ten examples of ridges and trenches from around the world.
Origins of the landform: Ocean ridges and trenches -- Mid-Atlantic Ridge, Atlantic Ocean -- San Juan de Fuca Ridge, Pacific Ocean -- Mariana Trench, Pacific Ocean -- Galápagos Rift, Pacific Ocean -- East Pacific Rise, Pacific Ocean -- Arctic Ridge, Arctic Ocean -- Iceland, North Atlantic Ocean -- Java Trench, Indian Ocean -- Peru-Chile Trench, Pacific Ocean -- Red Sea, North Africa and the Middle East -- Glossary -- Books -- Web sites -- Index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ocean bottom -- Juvenile literature; Mid-ocean ridges -- Juvenile literature; Deep-sea ecology -- Juvenile literature; Ocean bottom; Mid-ocean ridges; Deep-sea ecology; Electronic books; Electronic books